IMPACT OF NEEDS-BASED LEADERSHIP ON SME EMPLOYMENT ENTERPRISES (SMES) IN PANGKALPINANG - Nawanto, Condro; Triyono, Agus (Edunomika Journal : Studies In Education And Development Economics, 2026)
This study aims to analyze the impact of Needs-Based Leadership on employment stability and workforce performance within Small and Medium Enterprises (SMEs) in Pangkalpinang. Utilizing a quantitative approach with a survey method, data were gathered via structured questionnaires administered to a census sample of local SME actors and analyzed through simple linear regression and correlation frameworks. The narrative findings reveal that Needs-Based Leadership exerts a positive and highly significant influence on SME employment outcomes. The study demonstrates that when business owners actively address employees' hierarchical needs, ranging from essential job security during regional commodity fluctuations to self-actualization, it substantially enhances worker retention, motivation, and overall operational productivity. The correlation between responsive leadership and workforce stability proves to be exceptionally strong, indicating that the vast majority of variations in employee engagement are determined by this supportive leadership style. The novelty of this research lies in its empirical focus on a commodity-dependent regional transition economy, illustrating how localized, empathetic leadership serves as a vital economic shock absorber for workers facing market uncertainty. Implicatively, prioritizing humanistic human resource management over mere capital expansion is a strategic imperative for enterprise sustainability. This study contributes to the fields of economics and economic education by providing a clear framework on how fulfilling psychological needs translates directly into microeconomic resilience and sustainable local workforce development.